Positioning Uzbekistan as a global hub for education: Uzbekistan to convene the world summit on professional education - Abd Rahman, Shukran; Islamov, Shahzod (Human Assistance & Development International Inc. (HADI Inc.), 2025)
Uzbekistan's education is characterized by remarkable strengths, including the dynamic progress that stand out as Uzbekistan's competitive advantages in higher education. Since 2016, Uzbekistan has undergone a comprehensive reform of its higher education sector.